The mathematical problem solving ability of student on learning with Thinking Aloud Pair Problem Solving (TAPPS) model in term of student learning style - Mashuri, Mashuri; Nitoviani, Nindy Dwi; Hendikawati, Putriaji (Unnes Journal of Mathematics Education, 2018)
The purposes of this research were to find out the mathematical problem solving ability on learning with TAPPS model and to find out how the description of mathematical problem solving ability on TAPPS model in terms of learning style. This mixed methods research used concurrent embedded design. The population in this research was eighth-grade students of SMP N 4 Kudus in the academic year of 2016/2017. The sample was chosen by using random sampling technique, it obtained that VIIIA as experimental class and VIIIB as control class. The results of the research showed that (1) the mathematical problem solving ability on learning with TAPPS model achieved classical mastery, (2) the mathematical problem solving ability on learning with TAPPS model was better than expository model, (3) the students' ability in mathematical problem solving with a visual learning style had good category at the stage of devising a plan and the other stage had enough category, otherwise students with an auditorial learning style had enough category at the stage of looking back and another stage had good category, and students with a kinesthetic learning style had good category at the stage of understanding the problem and the other stage had enough category and less category.